Approximating a common zero of finite family of monotone operators in Hadamard spaces. (2nd December 2017) - Heydari, Mohammad Taghi; Khadem, Amene; Ranjbar, Sajad
Abstract: In this paper, a common zero of a finite family of monotone operators is approximated in Hadamard spaces. Some applications in convex minimization and fixed point theory are also presented.